Minimizing contrast agent dosage in CT angiography using a saline chaser with a low trigger threshold - Li, Linghan; Zhu, Xiaojian; Wu, Xunhua (Frontiers in Radiology, 2026)
BackgroundComputed tomography angiography (CTA), utilizing iodinated contrast agents, is a first-line diagnostic tool for cardiovascular diseases (CVD). However, the administration of contrast agents introduces potential risks to patients.ObjectiveThis study aims to design a novel protocol for CTA that integrates a saline chaser strategy and low-threshold triggering and evaluate, and demonstrate its feasibility and practicality minimizing the required contrast agent for imaging.MethodsA novel protocol for CTA incorporating a saline chaser strategy and low-threshold triggering was developed. Random assignment of eighty patients undergoing CTA examinations divided them into conventional and novel protocol groups. The assessment encompassed iodine intake, radiation dose, image quality, and superior vena cava artefacts in both cohorts.ResultsThe novel protocol group exhibited a noteworthy 20% reduction in iodine intake compared to the conventional group (P < 0.05, FDR correction). Notably, Hounsfield units (HU) of the ascending and descending aorta at the T12 level tended to be lower in the novel protocol group (P < 0.05, uncorrected), while parameters like signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) exhibited no significant between-group differences. Compared with conventional group, fewer superior vena cava artefacts were observed in the novel protocol group, and subjective image quality assessment by physicians remained consistent between the two groups (kappa = 0.84, P < 0.01).ConclusionThe combination of saline chaser strategy with low-threshold triggering in CTA imaging proves a viable approach, significantly curtailing the utilization of iodinated contrast agents, and superior vena cava artefacts.